Older adult listeners’ perception on the language used and quality of the programme at Wai FM Iban - Malia Taibi; Neilson Ilan Mersa; Remmy Gedat (Penerbit Universiti Kebangsaan Malaysia, 2022)
Community radio is still relevant in today's world despite the rapid changes taking place in communication information technology. It is a faster platform for disseminating information apart from other traditional media, mobile phone and the Internet. In Sarawak, Wai FM Iban is popular among the Iban community especially those living in rural areas. This is because it is the fastest way for the local community to obtain information. This study aims to examine how older adult listeners of Wai FM Iban evaluate the language used by the broadcasters and the quality of radio programmes produced by the radio station. As listening to the radio has become a daily activity among Iban community, Wai FM Iban has a vital role to play in disseminating information to the Iban community throughout Sarawak. It plays a role to ensure proper and correct Iban language is used on air. This study employs a qualitative approach where focus group discussion is used for data collection. Findings show that older listeners of Wai FM Iban are concerned about the use of code-mixing and code-switching among broadcasters that would lead to the deterioration of the language. Findings also indicated that older adult listeners are concerned about the quality of language used and programmes produced by the radio station. As the custodian of Iban language, custom and tradition, they believed that the language used by the broadcasters will determine the quality of programmes produced by the radio station.